The Relation Of Learning Discipline With Learning Results Of Hygiene, Sanitation And Sefty Work - Ade Anggraini; Elida Elida (Universitas Negeri Padang, 2021)
The research objective was to determine the relationship between learning discipline and student learning outcomes in the Hygiene, Sanitation and Work Safety Subjects at SMK Negeri 1 Padang Panjang. The research objective describes the learning discipline with learning outcomes. Grade X student of SMK Negeri 1 Padang Panjang. This type of quantitative research uses correlational methods. The population was 29 people and the sample technique used was total sampling. Student learning discipline data were obtained from a questionnaire arranged using a Likert scale model. While learning outcomes are obtained from report cards, namely a combination of knowledge values and skills scores. The type of data used in this research is Product Moment Correlation. Based on the results of the research conducted, it showed that the students' learning discipline of Hygiene, Sanitation and Work Safety Skills Competency of Catering at SMK Negeri 1 Padang Panjang was in the high category with a percentage of 52%, learning outcomes were in the medium category with a percentage of 69%. With a correlation value of 0.415. The results of the correlation coefficient test sig <0.05 or Tcount> T table, the hypothesis is accepted, on the other hand, if sig> 0.05 or Tcount <Ttable the hypothesis is rejected. The sighitung value 0.25 <0.05 with a value of Tcount = 2.370 and a Ttable value of N = 29 = 1.699, it is stated that 2.370> 1.699 with a significance of 0.025 <0.05. The hypothesis (Ha) is accepted, there is a positive and significant relationship between learning discipline and learning outcomes in the subject of Hygiene, Sanitation and Occupational Safety Skills Competency of Catering at SMK Negeri 1 Padang Panjang